Effects of feed manufacturing on nutrient metabolism, nutrient retention, and growth performance of broiler chickens - Rude, Christopher Mark (Kansas State University, 2011)
Broiler chicken feed is processed. Cereal grains are ground to reduce particle size and the feed usually is pelleted. When pelleted, broiler diets are steam conditioned and forced through a die causing varying levels of starch gelatinization. Cereal grain particle size and starch gelatinization can be controlled during feed manufacturing. Earlier research has shown that starch gelatinization negatively affects growth performance of 0 to 21 d of age. An experiment was conducted to determine the effects of corn particle size and starch gelatinization on growth performance, dressing percentage, and gizzard size when fed to 22 to 42 d of age broilers. Increasing particle size from 470 to 1240 μm increased body weight gain, dressing percentage, and relative gizzard size. Starch gelatinization increased relative gizzard size. No interaction effects were detected. To expand on previous experiments, a trial was conducted to investigate the effect of starch gelatinization on broiler chick gastrointestinal pH, glucose absorption, and glucoregulation. Starch gelatinization level affected jejunum pH, with a higher pH reported at 20% starch gelatinization. Increases in starch gelatinization decreased blood glucose and increased glucagon level. Highest measured glucagon level was reported in broiler chicks fed the diet with 20% starch gelatinization level diet after 6 hours of starvation. A third experiment was conducted to determine the effect of starch gelatinization on metabolizable energy and amino acid digestibility. Increasing starch gelatinization from 0 to 100% increased true metabolizable energy and fecal output in roosters. No effect was found on apparent metabolizable energy or amino acid digestibility, with an increase in starch gelatinization from 0 to 20%. Increasing particle size from 470 to 1240 μm had a positive effect on 22 to 42 d growth performance. A starch gelatinization level of 20% or lower had no effect on metabolizable energy or amino acid digestion. Older broilers with larger gastrointestinal tracts are unaffected by 20% gelatinized starch; whereas, 20% gelatinized starch reduced blood glucose and increased glucagon levels of young broilers. Lower blood glucose and increased glucagon are indicative of lower glucose storage, and could cause reduced young broiler growth performance when fed diets with gelatinized starch.
Keywords: Feed manufacturing; Feed particle size; Feed processing; Broilers; Poultry; Pelleting; Agriculture, General (0473)